2009
DOI: 10.1186/1756-0500-2-102
|View full text |Cite
|
Sign up to set email alerts
|

On the cytotoxicity of HCR-NTPase in the neuroblastoma cell line SH-SY5Y

Abstract: BackgroundThe human cancer-related nucleoside triphosphatase (HCR-NTPase) is overexpressed in several tumour tissues including neuroblastoma. HCR-NTPase is an enzyme exhibiting a slow in vitro activity in hydrolysing nucleosidetriphosphates. However, its in vivo function is still unknown. To learn more about the physiological role of HCR-NTPase, we both overexpressed and silenced it in the neuroblastoma cell line SH-SY5Y.FindingsNo effect was observed when the expression of endogenously expressed HCR-NTPase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…3 ). Interestingly, researchers have shown that NTPCR is overexpressed in neuroblastomas, 16 but no study has associated NTPCR with GBM. Additionally, one of the probe sets that had a non-zero coefficient estimate was designed to interrogate the gene PDZ and LIM domain 4 (PDLIM4), which has previously been studied in association with gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Interestingly, researchers have shown that NTPCR is overexpressed in neuroblastomas, 16 but no study has associated NTPCR with GBM. Additionally, one of the probe sets that had a non-zero coefficient estimate was designed to interrogate the gene PDZ and LIM domain 4 (PDLIM4), which has previously been studied in association with gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…NTPCR (THEP 1, C1orf57, or HCR-NTPase) is a non-specific nucleoside triphosphatase exhibiting a slow hydrolyzed activity in vitro . It is overexpressed in several tumor tissues including neuroblastoma and liver cholangiocarcinoma ( Placzek et al, 2007 ; Pasdziernik et al, 2009 ). A previous study reported there was no effect observed in NTPCR-silencing neuroblastoma cells, while overexpression of NTPCR led to the cytotoxicity of this protein ( Pasdziernik et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is overexpressed in several tumor tissues including neuroblastoma and liver cholangiocarcinoma ( Placzek et al, 2007 ; Pasdziernik et al, 2009 ). A previous study reported there was no effect observed in NTPCR-silencing neuroblastoma cells, while overexpression of NTPCR led to the cytotoxicity of this protein ( Pasdziernik et al, 2009 ). However, the expressed status and physiological role of NTPCR is still unknown in other cancer types, especially in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The other member of the Musashi gene family, Msi1, is not highly expressed in the SCN ( Table 2). Two of the FSS genes that are MSI2 targets (Table 2) are not well understood (Blcap and Ntpcr), but are expressed abnormally in cancer cells (Pasdziernik et al, 2009;Gromova et al, 2017), which tend to be poorly differentiated.…”
Section: Bioinformatics Indicate Significant Msi2 and Rna-binding Promentioning
confidence: 99%